EFFECTS OF POLICOSANOL ON SERUM LIPID LEVELS IN HEALTHY SUBJECTS: AN EXPLORATORY POST HOC ANALYSIS OF A DOUBLE-BLIND, PLACEBO-CONTROLLED, PARALLEL COMPARATIVE STUDY. - Hitoe, Shoketsu; Fernández Travieso, Julio César; Mendoza Castaño, Sarahi; Jung, Kwi Yeon (Revista CENIC Ciencias Biológicas, 2025)
Objective: Hypercholesterolemia is a major risk factor for coronary heart disease. There is evidence of the benefits of lowering cholesterol levels in subjects with borderline to mildly elevated serum total cholesterol (TC) levels (5.0-6.0mmol/L). Policosanol is a cholesterol-lowering drug made from purified sugar cane wax and now is also used as a cholesterol-lowering nutraceutical owing to its safety profile in some countries. The current exploratory post hoc analyses sought to investigate whether policosanol is efficacious to lower mildly elevated cholesterol levels at the normal ranges in healthy participants with borderline serum LDL-C levels, who previously participated in a randomized controlled trial. Methods: Data was obtained from a previous 14-week, single-center, prospective, double-blind, placebocontrolled, parallel-group, comparative study conducted in subjects with serum TC levels ≥ 4.8 to < 6.0mmol/L. After a six-week run-in period with instructions on lifestyle changes, participants were randomly assigned to two groups to receive either 5 mg of policosanol or placebo once daily with dinner for eight weeks. Lipid profile, safety indicators, adverse events (AEs), and treatment adherence were assessed. Data of thirty-nine participants were included in this analysis (policosanol = 16, placebo = 23). Results: After 8 weeks of supplementation, participants in the policosanol group exhibited statistically significant decreases in serum TC (-13.84%), LDL-C (-23.89%), LDL-C/HDL-C (high-density lipoprotein cholesterol) ratio (-30.45%) and increase in HDL-C (10.80%) versus baseline (week 0) while no significant changes were observed in the placebo group. The reductions on policosanol group were also significant compared to placebo. There were no significant changes observed on triglyceride. Conclusion: From the above results, it is concluded that policosanol supplementation has the potential to lower mildly elevated cholesterol levels at the normal ranges in healthy subjects and to be used as a cholesterol-lowering nutraceutical to improve the risk factor of hypercholesterolemia for coronary heart disease.